1999
DOI: 10.1177/002199839903301202
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of High Velocity Impact and Penetration Failure Modes in Textile Composites

Abstract: The dynamic failure evolution of textile composites, which were subjected to impact velocities up to 1100 m/s, was investigated. Specialized machines were used to fabricate composites from combinations of Spectra®, Kevlara®, and Twaron® fibers and two- and three-dimensionally woven, braided, and needle-punched nonwoven fabrics. This control of fabrication and processing enabled us to characterize response as a function of areal density, fabric finish, and consolidation techniques. Failure was categorized in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…Lee et al [7] noted in their ballistic study involving Spectra 900 R that although the matrix system did not seem to absorb substantial amounts of the impact energy, it definitely contributed to the overall amount of the energy absorbed by the composite. Flanagan et al [8] compared ballistic performance of various fabrics of different architectures, made of Spectra 1000 R , Kevlar 129 R , and Twaron 2000 R . An epoxy resin was used as the matrix system.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [7] noted in their ballistic study involving Spectra 900 R that although the matrix system did not seem to absorb substantial amounts of the impact energy, it definitely contributed to the overall amount of the energy absorbed by the composite. Flanagan et al [8] compared ballistic performance of various fabrics of different architectures, made of Spectra 1000 R , Kevlar 129 R , and Twaron 2000 R . An epoxy resin was used as the matrix system.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that 3D braided composites show better damage tolerance than quasi-isotropic laminates with approximate bending stiffness in the primary direction. Flanagan et al [14] carried out a high velocity impact experiment to investigate the damage mechanism in woven, 3D braided and needle punched composites under impact velocities ranging from 200 to 1100 m/s. The penetration resistance and failure modes of these different textile composites were analyzed and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although there exist a number of publications related to high velocity impacts on monolithic (i.e. non-hybrid) compliant laminates [9][10][11][12][13][14][15][16][17], only few are related to design of novel hybrid structures.…”
Section: Introductionmentioning
confidence: 99%